Tricarina gadvanensis is an isopod: reinterpretation of an alleged lobster from the Lower Cretaceous of Iran. (March 2020) - Hyžný, Matúš; Audo, Denis; Feldmann, Rodney M.; Schweigert, Guenter
Abstract: An incomplete arthropod fossil, Tricarina gadvanensis Feldmann et al., 2007, from the Lower Cretaceous (Barremian–Aptian) of Iran, originally interpreted as a lobster (Malacostraca, Eucarida, Decapoda), is reinterpreted herein as a representative of a seroloid isopod crustacean (Malacostraca, Peracarida, Isopoda). The body orientation of the fossil is reversed, and the alleged cephalothoracic shield is reinterpreted as being the pleotelson. Tricarina gadvanensis, with its unique configuration of pleonite fusion (pleonites 1–4 are free, whereas pleonite 5, with still visible epimera, is fused with the pleotelson), is suggested to represent a close relative of Serolidae. The preservation of T. gadvanensis in deepwater shales speaks for conservativeness in environmental preferences of seroloid isopods for at least 125 million years.